The Correlation of Model-Based Insulin Sensitivity and Respiratory P/F Score - Abu-Samah A.; Razak A.A.; Razak N.N.; Suhaimi F.M.; Jamaludin U. (Springer Science and Business Media Deutschland GmbH, 2023)
Biomedical engineering; Correlation methods; Diagnosis; Safety engineering; Critically-ill patients; General patterns; Insulin resistance; Insulin sensitivity; Pearson correlation; Respiratory failure; Respiratory function; Respiratory organs; Insulin